ANALYSIS OF MISTAKE IN TEXT NARRATION (EXPLORERS) JUNIOR HIGH SCHOOL STUDENT - Ida Hamidah; Rizki Triranti Yunesi; Yunita Fitriani Fasya (JLER (Journal of Language Education Research), 2018)
This study aims to determine the ability of students in applying the rules of language in writing narrative text (exemplum). This study is limited to the analysis of language errors on aspects of spelling, morphology, and syntax. The formulation of this research problem are: 1) What is the mistake of the language done by junior high school students in the field of morphology?; 2) What is the mistake of language done by junior high school students in the field of syntax?; 3) What is the mistake of language done by junior high school students in the spelling field?; 4) What steps should the teacher undertake to improve students' skills in these linguistic areas? This study aims 1) Knowing the language errors that students do in the field of morphology, syntax, and spelling. 2) Finding the right solutions to overcome the problem of the low ability of students in terms of language in written essay students. 3) Provide inputs to the authorities regarding the results of research related to the low understanding and skills of students in applying the concepts of language in written students made. This study used the descriptive qualitative method. Based on the research found that there are some language errors in the text exemplum made students, namely on the level of morphology, syntax, and spelling.